Evolving Normative Dynamics: Understanding China's Varied Approaches to Overseas Corporate Social Responsibility in the Belt and Road Initiative Era - Yue Lin (Journal of Current Chinese Affairs)
China's Belt and Road Initiative (BRI) is nowadays a global development initiative, with which China pursues a new international identity as a “responsible major country.” The inadequate fulfilment of corporate social responsibility (CSR) in BRI partner countries however has tainted the BRI's cooperative “win–win” principle and sparked external legitimacy crises. This study explores how Chinese policymakers respond to overseas CSR challenges in the realms of environmental and societal responsibility. By integrating both constructivist and rationalist elements, we employ three key variables to facilitate cross-case comparisons. Our analysis reveals that China has favoured a parallel overseas CSR governance system that allows for tailored responses to specific contexts. China's nuanced approaches to international CSR standards reflect rational decisions influenced by issue-specific domestic–international normative fit, perceived legitimacy of the relevant international regime, and the significance of each issue to China's global status. This research offers insights into China's contextualised engagement with international CSR norms in the BRI era.